UbiD domain dynamics underpins aromatic decarboxylation - Stephen A. Marshall (Nature Portfolio, 2021)
Understanding the structure and dynamics of enzymes is important for a number of applications. Here, the authors report on the crystal structure of vanillic acid decarboxylase, and show how the dynamics of the UbiD superfamily enzymes relate to the covalent catalysis of aromatic (de)carboxylation.